2010
DOI: 10.4196/kjpp.2010.14.1.29
|View full text |Cite
|
Sign up to set email alerts
|

MLCK and PKC Involvements via Gi and Rho A Protein in Contraction by the Electrical Field Stimulation in Feline Esophageal Smooth Muscle

Abstract: W e have shown that myosin light chain kinase (MLCK) was required for the off-contraction in response to the electrical field stimulation (EFS) of feline esophageal smooth muscle. In this study, we investigated whether protein kinase C (PKC) may require the on-contraction in response to EFS using feline esophageal smooth muscle. The contractions were recorded using an isometric force transducer. On-contraction occurred in the presence of N G -nitro-L-arginine methyl ester (L-NAME), suggesting that nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
2
7
1
Order By: Relevance
“…The present study shows that LPA is closely involved with endogenous NO release, which causes relaxation via an LPA 1 receptor-mediated pathway in LES, which is consistent with the findings of a previous study, in which it was found that EFS stimulates NO release (Park et al, 2009(Park et al, , 2010. Because recent studies have concluded that NO, rather than VIP, is the major mediator of nerve-induced smooth muscle relaxation (Uc et al, 1999), we examined the effects of LPA on the direct NO-induced relaxation of LES using SNP (a NO donor) as relaxant, and significant inhibition of SNP-induced relaxation was observed in an LPA concentration-dependent manner in cat LES.…”
Section: Discussionsupporting
confidence: 94%
“…The present study shows that LPA is closely involved with endogenous NO release, which causes relaxation via an LPA 1 receptor-mediated pathway in LES, which is consistent with the findings of a previous study, in which it was found that EFS stimulates NO release (Park et al, 2009(Park et al, , 2010. Because recent studies have concluded that NO, rather than VIP, is the major mediator of nerve-induced smooth muscle relaxation (Uc et al, 1999), we examined the effects of LPA on the direct NO-induced relaxation of LES using SNP (a NO donor) as relaxant, and significant inhibition of SNP-induced relaxation was observed in an LPA concentration-dependent manner in cat LES.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast to the basal tone in human and cat lower esophageal sphincter, ACh-and EFS-induced phasic contraction in the esophageal body is primarily mediated by PKC (12,25,37). Similar conclusions were drawn by the inhibition of carbachol-induced contraction of urinary bladder by PKC inhibitor (7).…”
Section: Discussionsupporting
confidence: 63%
“…[In contrast to the phasic activity in RSM, a number of studies have shown that basal tone in the lower esophageal sphincter and IAS in humans and animals is mediated primarily via the RhoA/ROCK pathway (25,30,32,37).] The present data also show selectivity of the effects of PKC and ROCK inhibitors on the respective pathways.…”
Section: Discussioncontrasting
confidence: 38%
“…In vitro studies of human esophageal strips using direct activation of enteric motor neurons by electrical field stimulation (EFS) have shown that lower esophageal smooth muscle relaxation is mainly caused by NO released from inhibitory enteric motor neurons, whereas esophageal contraction is mainly caused by acetylcholine released from excitatory enteric motor neurons acting on muscarinic receptors located in the smooth muscle [3,[28][29][30]. Except for acetylcholine, other neurotransmitters influence EFS-induced contraction in esophageal smooth muscle.…”
Section: Introductionmentioning
confidence: 99%